Predictors of upper limb spasticity after stroke? A systematic review and meta-analysis. Issue 2 (June 2019) - Tedesco Triccas, Lisa; Kennedy, Niamh; Smith, Toby; Pomeroy, Valerie
Abstract: Objective: To determine the predictive markers for the occurrence of upper limb spasticity in the first 12 months after stroke. Data sources: A systematic review was undertaken of the databases MEDLINE, EMBASE, CINAHL and PEDRO to 31st December 2017. Study selection: Non-experimental or experimental studies that included a control group with spasticity who did not receive an experimental intervention which investigated at least one variable (explanatory variable) measured at baseline against the development (or not) of spasticity at a future time point within 12 months post stroke were selected independently by two reviewers. Eleven papers met the selection criteria. Study appraisal: Data were extracted into tabular format using predefined data fields by two reviewers. Study quality was evaluated using the modified Downs and Black tool. Data were analysed using a meta-analysis or narrative review. Results: Ten studies, including 856 participants were analysed. The predictive markers of upper limb spasticity at one month post stroke were: motor 11.25 (odds ratio, OR); [95% CI:2.48, 51.04] and sensory impairments 4.91 (OR); [1.24, 19.46]; haemorrhagic stroke 3.70 (OR); [1.05, 12.98] and age 0.01 (OR) [0.00, 69.89]. Only motor impairment was found as a significant predictor at six months post stroke 30.68 (OR); [1.60, 587.06]. Limitations: Low number of studies exploring biomechanical and neurophysiological in addition to behavioural predictors of spasticity were included. Conclusion and implications of key findings: Using the results, the identified predictive markers have potential to better inform clinical decision-making and to plan specific rehabilitation interventions by physiotherapists for stroke survivors with upper limb spasticity. Systematic Review Registration Number PROSPERO (ID: CRD42016027642).